Burkholderia pseudomallei Type G in Western Hemisphere - Jay E. Gee; Christopher J. Allender; Apichai Tuanyok; Mindy G. Elrod; Alex R. Hoffmaster (Emerging Infectious Diseases, 2014)
Burkholderia pseudomallei isolates from the Western Hemisphere are difficult to differentiate from those from regions in which melioidosis is traditionally endemic. We used internal transcribed spacer typing to determine that B. pseudomallei isolates from the Western Hemisphere are consistently type G. Knowledge of this relationship might be useful for epidemiologic investigations.